Studi Kualitatif Praktik Kesehatan Selama Menstruasi Pada Siswi MTS 01 Pondok Pesantren Darussalam - Misniarti Misniarti; Sri Haryani (Poltekkes Kemenkes Bengkulu, 2021)
Health practices during menstruation are an important issue. These practices consist of garbage disposal, water sanitation, and student behavior during menstruation. If the practice is not carried out properly, it will have a negative impact on the physical health and reproductive health of adolescents. This study aims to determine health practices during menstruation in female students at the Darussalam Islamic Boarding School in Kepahiang Regency. The method used is a qualitative study with a phenomenalogy approach. The sample consisted of 7 students who have experienced 6 menstrual periods and are willing to become informants, 1 UKS officer graduated from nursing school and 2 boarders who live in the dormitory. The analysis used is the Colaizzi technique. The results of this study obtained three themes, namely personal hygiene practice, exercise practice and fulfillment of nutrition during menstruation. The conclusion of this study is that the personal hygiene practices of most informants have been done correctly. Most of the informants did not exercise and inadequate fulfillment of nutrition during menstruation. Based on the results of this study, nurses who one of them role as education providers should hold educational classes for teachers, mothers and female students about adolescent problems and proper care, prepare independent educational materials that focus on personal hygiene practices, exercise and fulfillment of nutrition during menstrual period.